Para uma análise crítica da democracia participativa na constituição de 1988 sob a perspectiva da filosofia política de Bobbio - Melo, Martinho Ramalho de (2021)
This dissertation work has as its general objective and object to perform a critical analysis of the Participatory Democracy institutes inserted in the Constitution of the Federative Republic of Brazil of 1988. Norberto Bobbio and his political philosophy are the presente reference and counterpoint of this work, and with him – and also against it - institutes of Participatory Democracy inserted in the Constitution (such as, e.g., plebiscite, referendum, popular initiative, among others less relevant) will be analyzed in the context of the Democratic State of Law created in 1988. The research problem is to know whether or not such institutes expanded (and why) our Democracy. We have as the hypothesis regarding the proposed problem that this expansion was not only insufficient but, objectively, it urgently needs to be expanded. Regarding the method, it is a bibliographical research, of an analytical and qualitative character of the mentioned institutes and participative mechanisms and the limits and possibilities of its use and expansion, with which the preliminary analysis of participatory democracy concludes by the importance of its pioneer presence in the Brazilian Constitution, but noting its insufficiency for the expansion and enlargement of Democracy. The theoretical framework – also a counterpoint – is based on Bobbio's political philosophy, also drawing on classical and modern Political Philosophers, notably in those aspects of its reception in our guiding author's political philosophy. The general objective of the research, mentioned above, is reflected in the specific objectives, worked out chapter by chapter: the first, which makes a synthetic overview of Bobbio's political philosophy; the second examines the core elements, in Bobbio, of the so-called “Representative Democracy”. The third chapter reflects the specific objective of examining the counterpoint offered by Participatory Democracy. The fourth chapter (reflecting the corresponding final specific objective) intends to treat and criticize representation (paraphrasing Nélson Rodrigues) as “life as it is” – we would better say “as it is being” in purely formal democracy. Finally, and as a synthesis of the specific objectives expressed in the chapters, it is concluded by pointing out prescriptively how a Democracy, which has the demos as its center and objective, should be (or, now paraphrasing Engels, as “things could not have been”).